Autism and social disconnection in interpersonal rocking - Marsh, Kerry L.; Isenhower, Robert W.; Richardson, Michael J.; Helt, Molly; Verbalis, Alyssa D.; Schmidt, R. C.; Fein, Deborah (Frontiers in Integrative Neuroscience, 2013)
Individuals with autism spectrum disorders (ASD) have significant visuomotor processing deficits, atypical motoric behavior, and often substantial problems connecting socially. We suggest that the perceptual, attentional, and adaptive timing deficiencies associated with autism might directly impact the ability to become a socially connected unit with others. Using a rocking chair paradigm previously employed with typical adults, we demonstrate that typically-developing (TD) children exhibit spontaneous social rocking with their caregivers. In contrast, children diagnosed with ASD do not demonstrate such a spontaneous pull to a symmetrical rocking state with their parents. We argue that the movement of our bodies is one of the fundamental ways by which we connect with our environment and, especially, ground ourselves in social environments. Deficiencies in perceiving and responding to the rhythms of the world may have serious consequences for the ability to become adequately embedded in a social context.